Estado de natureza em Vidas secas, de Graciliano Ramos: o realismo humanista do cotidiano brasileiro - Gerlin, Caio Gobbi (2021)
The present work analyzes the relationship between art and society in which one affects the other. It is in everyday life that art has its inspiration and makes itself present. Through this perspective, the work Vidas secas was analyzed and the Brazilian historical circumstances that this impacting narrative of Velho Graça represents in the field of literary autonomy. The theoretical interlocution, besides the critical fortune on the fictional production of Graciliano Ramos, will take place mainly in interfaçe Thomas Hobbes and Georg Lukács. With the former, the dialogue will be triggered with the category of the State of nature, developed in the work Leviathan (1651). It is not the intention of this researcher, it must be emphasized, to accept Hobbes' arguments; on the contrary, the objective is to appropriate his analyses, having in mind the following challenge: to show how the historical conditions of Brazil - a colonized country that until now has been bled by foreign powers - condemns a good part of its population to the tragic conditions of a historical State of nature. Thus, this research defends the "State of human history" in its interaction with nature. With the latter, in turn, the dialogical interaction will take place in view of the categories of aesthetic realism developed by the Hungarian thinker during much of his life. With this, it is assumed that the literary work of reference of this study is a singular example of Brazilian aesthetic realism.